Parasitic nematodes associated to tomato plants in western Nicaragua. - Salazar-Antón, Wilber; Guzmán-Hernández, Tomás de Jesús (Agronomía Mesoamericana, 2013)
The objective of this study was to iden-tify parasitic nematodes associated with the tomato crop in Leon and Chinandega western region of Nicaragua. During the period of 2010-2011, five tomato fields were sampled in both Leon and Chinandega; these samples included soil and roots, the total sampled area was of 2.5 ha. Eight samples were collected from each of the ten tomato plantations studied, for a total of 80 samples. Soil and root samples were taken 10 m from each other in a zig-zag pattern. Soil nematode extraction was conducted using the Modified Baermann funnel technique and maceration and sieving method was used for root nematodes. The data obtained was correlated with predisposing factors that have been reported to influence nematodes such as soil type, crop rotation and precipitation. Similarly, the population growth of the main nematode genera was described through mathematical models. The greatest densities of nematodes were isolated from soil samples; the most common nematodes in 100 grams of soil were Meloidogyne with 739, Pratylenchus with 555, Tylenchorhynchus with 386 and Helicotylenchus with 252. It was proven that precipitation had no significant effect on the parasitic nematode population. Finally, it was determined that the increasing number of Meloidogyne and Pratylenchus in the tomato crop fit a linear mathematical model (R2=0,98 for both nematodes), showing an existing positive and linear correlation between the phenological stages of the tomato and the increment of the nematodes in the soil.